Validation Data of Mexico's Trade Balance - PRATS, Germán MARTÍNEZ; ARMENTA-RAMÍREZ, Aida Beatriz (Journal of Advanced Research in Law and Economics; Vol 10 No 4 (2019): JARLE Vol X Issue 4(42) Summer 2019, 2019)
The collection, compilation and dissemination of international merchandise trade statistics must follow standards for international comparability. These processes are structured according to particular institutional arrangements in countries. The general responsibility and dissemination of the Merchandise Trade Balance in Mexico are Tax Administration Service, Ministry of the Economy, Banco de México and the National Institute of Statistics and Geography. At most points of entry, goods are brought into or withdrawn from the customs territory of a country under various customs procedures. The objective of this paper is to establish a method of validation of imports and exports considering the volumes by tariff fraction and unit of measure, as well as the incoterms, to generate a specific registry that allows obtaining more reliable information and serves to make decisions of the actors involved in foreign trade. This information will be used to analyze the evolution and structure of the Commercial Balance of Mexico, as well as to evaluate the interaction that is registered between the commercial activity and the behavior of the national economy, that is why the analysis of the information it generates the commercial balance of Mexico, since this is basic for the decision making of those in charge of public policies in commercial and financial matters.